Cooperation between school and parents of SLI children - Lazarevic, Emilija; Kopas-Vukašinović, Emina (International Journal about Parents in Education, 2023)
Starting school is a significant turn-point in the life of every child, especially so for children with speech-linguistic impairments (SLI) and their parents. The cooperation between the parents and the teacher heavily influences school attainments of such children. This, of course, means that constant help of professional speech therapists is also necessary in order to eliminate or reduce maximally the consequences of the detected disorders. School attainment of these students is largely determined by their speech-linguistic development and particular impairments. Hence this paper focuses on basic manifestations of the most common disorders and, in the same context, on the duties of the teacher in relation to the parents of the SLI children. It is necessary that the teacher achieve a continuous cooperation with the parents in order to enable the SLI students to integrate into school environment as fully as possible. Suggested are some measures for improving the quality of teacher-parent relations which can stimulate the progress and development of the SLI students, especially in the sphere of their socio-emotional development. This includes the development of their emotional stability, sense of security, acceptance and satisfaction.